Clinical and Demographic Profile of Patients Receiving ECT in an Institute - Sherchan, S; Joshi, D (Journal of Nepal Health Research Council, 2009)
Background: Despite being an effective and safe treatment for severe psychiatric disorders, the use of electroconvulsive therapy (ECT) in different countries and different institutions has been uneven. More-over, in developed countries its use has clearly shown a declining trend. Methods: This retrospective study using ECT case record book has sought to find out the clinical and demographic profile of patients receiving ECT at the Mental Hospital in Lagankhel, Lalitpur and also to determine the trend of its use in last 10 years. Two ECT case record books which covered the time period from 1999 to 2008 were studied. Retrospective data necessary for this study was collected from those records. Results: The total number of ECT received in the year 1999 was 902 while it was 242 in the year 2008. The number of patients receiving ECT in the year 2008 was 44 patients with the diagnosis of acute psychosis and schizophrenia while only 20 patients with the diagnosis of affective disorder (mania and depression) out of total 64 patients. Conclusion: The study showed declining trend of the use of ECT in the state Mental Hospital as in developed countries but in contrast to affective disorder, acute psychosis and schizophrenia were the predominant clinical conditions where ECT was used. Key words: Direct/Unmodified, Electroconvulsive Therapy, Psychiatric disorders, Psychotropic medications DOI: 10.3126/jnhrc.v7i1.2272 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 10-13